2022
DOI: 10.1002/jso.27082
|View full text |Cite
|
Sign up to set email alerts
|

Current trends in nonoperative management for rectal adenocarcinoma: An unequal playing field?

Abstract: Background and Objectives Increasing evidence suggests patient‐oriented benefits of nonoperative management (NOM) for rectal cancer. However, vigilant surveillance requires excellent access to care. We sought to examine patient, socioeconomic, and facility‐level factors associated with NOM over time. Methods Using the National Cancer Database (2006–2017), we examined patients with Stage II–III rectal adenocarcinoma, who received neoadjuvant chemoradiation and received NOM versus surgery. Factors associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…It has been suggested that the MRI report should include precise prose description of internal and external sphincter muscle invasion, that invasion of the internal sphincter muscle and intersphincteric space should not be assigned a cT stage, and that invasion of the external sphincter complex, puborectalis, or levator muscle should be staged cT4b. 7,12 Clinical TN and MRF restaging by MRI after NT has been shown…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the MRI report should include precise prose description of internal and external sphincter muscle invasion, that invasion of the internal sphincter muscle and intersphincteric space should not be assigned a cT stage, and that invasion of the external sphincter complex, puborectalis, or levator muscle should be staged cT4b. 7,12 Clinical TN and MRF restaging by MRI after NT has been shown…”
Section: Resultsmentioning
confidence: 99%
“…Interpreting depth of extramural tumor invasion in the lowermost rectum is challenging because of the close proximity of the internal sphincter, intersphincteric plane, and external sphincter muscles. It has been suggested that the MRI report should include precise prose description of internal and external sphincter muscle invasion, that invasion of the internal sphincter muscle and intersphincteric space should not be assigned a cT stage, and that invasion of the external sphincter complex, puborectalis, or levator muscle should be staged cT4b 7,12 …”
Section: Discussionmentioning
confidence: 99%